2022
DOI: 10.7759/cureus.24438
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID-19 Multisystem Inflammatory Syndrome in Children and Adults: What Happens After Discharge?

Abstract: Introduction Classification criteria and practice guidelines for inpatient management of multisystem inflammatory syndrome (MIS) exist, but reports on outpatient management and clinical outcomes are lacking. Here we describe the management and clinical outcomes of four children and four adults with MIS seen at Walter Reed National Military Medical Center (WRNMMC) from diagnosis to six months follow-up. Methods This retrospective, case-series describes the initial presentation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Coronary abnormalities were also improved in most of the cases within 3 months [37]. Almost a complete recovery was reported 6 months after the discharge among MIS-C patients [115 ▪ ]. More than 50 patients are being followed in our center for more than 2 years, but no significant sequel has been noted, thus far.…”
Section: Outcomementioning
confidence: 70%
“…Coronary abnormalities were also improved in most of the cases within 3 months [37]. Almost a complete recovery was reported 6 months after the discharge among MIS-C patients [115 ▪ ]. More than 50 patients are being followed in our center for more than 2 years, but no significant sequel has been noted, thus far.…”
Section: Outcomementioning
confidence: 70%
“…Several studies demonstrated that a prolonged pro-inflammatory state, which is characterized by the increase in inflammatory markers, such as IL-1β, IL-6, and TNF-α, is a distinctive feature of patients with long COVID-19 [ 12 ] since these inflammatory alterations have been shown to persist in some patients for several months after infection, leading to a condition clinically known as post-COVID-19 multisystem inflammatory syndrome (MIS) or a systemic inflammatory response (SIR) [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%